Doubt flap technique in pterygium surgery - Abdulgani , Ahmed (Diyala Journal of Medicine, 2023)
Background: A pterygium is a triangular fibrovascular sub-epithelial ingrowth of degenerative bulbar conjunctival tissue over the limbus onto the cornea. The mainstay of treatment is surgery with more measures to decrease the recurrence rate. Pterygium doesn’t need intervention unless there is an extension of the lesion towards the center of the cornea and it encroaches on the visual axis, or is symptomatic in terms of redness and discomfort. Objective: To present a new surgical technique for managing primary pterygium. We aim to find a more effective method than the one previously used. We wanted to demonstrate and prove that this technique has low recurrence rates. Patients and Methods: A Hospital-based interventional case series study, sampling done by simple random sampling from the outpatient departments. The study was conducted in the ophthalmology department of Erbil teaching hospital in Erbil city for eight months from August 2021-April 2022. In the current study 40 patients with pterygium were operated that they were attending the ophthalmology department in this hospital. Results: The result revealed 3 cases of recurrence of 7.5% out of 40 cases using a dual flap technique as a new approach for treating pterygium in the follow-up of 3 months, in which the mean ± SD of age was 46.3 ± 10.537 years. Twenty four cases were female, and 16 were male; all of the lesions were nasally located pterygium. In the sample we used in the study 5 patients had had pterygium excision using other techniques in the past at least once, and neither of them recurred utilizing this approach. Conclusion: The double flap is a proper alternative technique in pterygium surgery; this new procedure, dual conjunctival flap with 7.5% recurrence rates and provides safe and comparable results to current methods.